2020
DOI: 10.1101/2020.08.22.261263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Active Perception during Angiogenesis: Filopodia speed up Notch selection of tip cellsin silicoandin vivo

Abstract: How do cells make efficient collective decisions during tissue morphogenesis? Humans and other organisms utilize feedback between movement and sensing known as 'sensorimotor coordination' or 'active perception' to inform behaviour, but active perception has not before been investigated at a cellular level within organs. Here we provide the first proof of concept in silico/in vivo study demonstrating that filopodia (actin-rich, dynamic, finger like cell-membrane protrusions) play an unexpected role in speeding … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 106 publications
1
6
0
Order By: Relevance
“…Consistent with this idea, preventing phosphorylation of Y820 via either mutation of Y820, R817, or via pharmacological inhibitors both inhibited c-Src activation and the ability of VEGFR-2 to stimulate filopodia formation in HEK-293 cells and PAE cells. Formation of filopodia protrusions is a key step for many angiogenic responses of endothelial cells such as sprouting and cell migration (Fischer et al, 2019;Zakirov et al, 2021). In agreement with observation, a recent study demonstrated that mice selectively deficient for c-Src in endothelial displayed significantly reduced blood vessel sprouting and loss in actin-rich filopodial protrusions (Schimmel et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…Consistent with this idea, preventing phosphorylation of Y820 via either mutation of Y820, R817, or via pharmacological inhibitors both inhibited c-Src activation and the ability of VEGFR-2 to stimulate filopodia formation in HEK-293 cells and PAE cells. Formation of filopodia protrusions is a key step for many angiogenic responses of endothelial cells such as sprouting and cell migration (Fischer et al, 2019;Zakirov et al, 2021). In agreement with observation, a recent study demonstrated that mice selectively deficient for c-Src in endothelial displayed significantly reduced blood vessel sprouting and loss in actin-rich filopodial protrusions (Schimmel et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…While some candidate mechanosensors such as the glycocalyx or mechanosensitive ion channels are essentially associated with individual cells, others such as cell–cell junctions are more suggestive of collective behaviour [ 36 , 347 ]. Recent evidence on the role of filopodia under VEGF stimulation [ 348 ] has set the course for a promising line of research. ECs sense and react to a VEGF stimulus individually, developing filopodia within seconds.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Filopodia, in turn, increase EC sensitivity to VEGF, amplifying differences in the input signal. This mechanism determines cell fate, supported by Notch signalling in a subsequent stage [ 348 ]. Based on this study, we suggest that the effects of IF around a microvessel could be explained by a similar process, with filopodia acting as flow sensors.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…The agent‐based memAgent‐spring model developed by Bentley et al (2008) has been incorporated in various computational models of sprouting angiogenesis to study different mechanisms affecting of VEGF/Notch and endothelial tip cell selection, including the regulation of VE‐Cadherin dynamics (Bentley et al, 2014), VEGF‐driven positive feedback through tetraspanin (Page et al, 2019), and active perception during angiogenesis through filopodia (Zakirov et al, 2021).…”
Section: Models Of Blood Vessel Sprouting and Formation At The Tissue...mentioning
confidence: 99%